Diminishing returns limit energetic costs of climate change. Issue 5 (May 2017) - Levy, Ofir; Borchert, Jason D.; Rusch, Travis W.; Buckley, Lauren B.; Angilletta, Michael J.
Abstract: Changes in the time available for organisms to maintain physiologically preferred temperatures (thermal opportunity) is a primary mechanism by which climate change impacts the fitness and population dynamics of organisms. Yet, it is unclear whether losses or gains in thermal opportunity result in proportional changes in rates of energy procurement and use. We experimentally quantified lizard food consumption and energy assimilation at different durations of thermal opportunity. We incorporated these data in an individual‐based model of foraging and digestion in lizards to explore the implications of nonlinear responses to shifts in thermal opportunity across a wide geographic range. Our model predicts that shifts in thermal opportunities resulting from climate change alter energy intake primarily through digestion rather than feeding, because simulated lizards were able to fill their gut faster than they can digest their food. Moreover, since rates of energy assimilation decelerate with increasing thermal opportunity, shifts in daily energetic assimilation would depend on the previous opportunity for thermoregulation. In particular, the same changes in thermal opportunity will have little impact on lizards from warm locations, while having a large impact on lizards from cold locations where thermoregulation is possible for only a few hours each day. Energy expenditure followed spatial patterns in thermal opportunity, with greater annual energy expenditure occurring at warmer locations. Our model predicts that lizards will spend more energy under climate change by maintaining higher body temperatures and remaining active longer. However, the predicted changes in energy assimilation following climate change greatly exceeded the predicted increases in energy expenditure. Simple models, which assume constant rates of energy gain during activity, will potentially mislead efforts to understand and predict the biological impacts of climate change.